1982
DOI: 10.1093/ajcn/36.4.576
|View full text |Cite
|
Sign up to set email alerts
|

The folate in human milk

Abstract: In previous studies of the folate content of human milk, samples were prepared for assay by a method that resulted in a turbid solution that was then assayed by a turbidimetric microbiological method. We have used an improved microbiological assay in which the milks were treated with rennin to precipitate casein and heated in a buffered ascorbate to coagulate lactalbumin and lactoglobulin. Milks were obtained serially from nursing mothers for periods ranging from 1 day to 6 months postpartum. The results showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

1986
1986
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Folate content in breastmilk (collected until 1 year postpartum) from North America, 22,24,25 Asia, 31,32 the United Kingdom, 33 and human immunodeficiency virus-positive mothers in South Africa 21 ranged from 55 to 365 nmol/L. The presented data for folate content (sum of folates) in Swedish breastmilk samples were in the middle of the range of the literature values.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Folate content in breastmilk (collected until 1 year postpartum) from North America, 22,24,25 Asia, 31,32 the United Kingdom, 33 and human immunodeficiency virus-positive mothers in South Africa 21 ranged from 55 to 365 nmol/L. The presented data for folate content (sum of folates) in Swedish breastmilk samples were in the middle of the range of the literature values.…”
Section: Discussionmentioning
confidence: 68%
“…The high between-sample variation in the present trial (range, 56-254 nmol/L) could be attributed to variations in breastmilk folate content during one nursing session, 1 day, and the whole lactation period. 22,25,34 The only information available to us was that all breastmilk was collected within 3 months postpartum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reports in the literature show that concentrations of other B‐vitamins such as thiamin (R oth ‐M aier et al 1996) or vitamin B 6 (K irchgessner et al 1996) in milk are also markedly influenced by the supplementary level during lactation. In lactating women, concentrations of various B‐vitamins such as thiamin and riboflavin (D ostalova 1988), vitamin B 6 and B 12 (S need et al 1981), biotin (G oldsmith et al 1982), folic acid (C ooperman et al 1982) and pantothenic acid (J ohnston et al 1981) also have been shown to be influenced by the intake during the lactation period. Consequently, it can be concluded that the intake of B‐vitamins during lactation influences their concentrations in milk.…”
Section: Discussionmentioning
confidence: 99%
“…Sawaya et al (1984),Mohamed et al (2005),Faye et al (2008),Haddadin et al (2008) andKonuspayeva et al (2010).3 Hill & Morrissey(2011); Morrissey & Hill (2011a,2011b), Nohr et al (2011a-g), Sauvant et al (2011), van Staveren & de Groot (2011) and Witthöft(2011).4 Lakdawala & Widdowson (1977),Cooperman et al (1982),Byerley & Kirksey (1985),Haskell & Brown (1999),Korchazhkina et al (2006) andNohr et al (2011a-g).…”
mentioning
confidence: 99%